Can Mental Index be used on CBCT images to determine sexual dimorphism? - Ana Luiza Esteves CARNEIRO; Sabrina Evelyn Santos MACIEL; Daniela Miranda Richarte de Andrade SALGADO; Jéssica Rabelo Mina ZAMBRANA; Nataly Rabelo Mina ZAMBRANA; Claudio COSTA (Faculdade São Leopoldo Mandic, 2020)
ABSTRACT Objective: Radiomorphometric indices (RI) vary according to gender and age. The objective of this study was to assess bone quality in men and women, using tomographic images Methods: A total of 78 Cone Beam Computed Tomography (CBCT) images of female and male patients were analyzed. The images were obtained from LAPI-FOUSP database, São Paulo, Brazil, and the Mental Index, which is a quantitative index, was evaluated on those images. The images were divided into 2 groups: Group M - Men and Group W - Women and evaluated by one examiner in two different times (T1 and T2). The data was submitted to a statistical analysis with a 95% level of significance (p <0.05) Results: The ICC tests showed an average to good intra-examiner agreement. The age averages were: 48.46 ± 15.3 for group W and 53.87 ± 13.09 for group M. On the MI evaluation, statistically significant differences were observed between the two groups Conclusion: We concluded that MI can be used to determine sexual dimorphism, once the thickness of the mandible cortex in women is smaller than the thickness found in men.